"Their Pets Are Loved Members of Their Family": Animal Ownership, Food Insecurity, and the Value of Having Pet Food Available in Food Banks. (2nd October 2017) - Rauktis, Mary Elizabeth; Rose, Lynda; Chen, Qi; Martone, Rachel; Martello, Amy
ABSTRACT: National estimates of household food security fail to take into account the animals in the household, and studies conducted by animal welfare, veterinary, and pet product associations have not estimated the extent to which pets experience food insecurity. Yet the proliferation of dedicated pet food pantries and the addition of pet food to existing food banks suggest that many pet owners are challenged to keep food on the table and in the food bowl. This descriptive study evaluated the pet food distribution program "Chow Wagon" by surveying the staff of participating food pantries and banks. The respondents provided their perception of the value of having pet food available in their food banks, as well as what additional animal services were needed. In addition, the study utilized Geographic Mapping Information (GIS) with United States Census data on poverty to assess the greater community need. The survey was mailed to 29 Chow Wagon participating food banks and 19 respondents completed a survey for a 61% response rate. According to the respondents, pet food availability in the food bank was highly valued by the clients, and when they did not have pet food, approximately three-fourths believed that their clients were likely to share human food with their pets. The findings were inconclusive about whether having pet food available prevents owners from surrendering their animals. Finally, GIS mapping of the region to identify areas of high poverty with limited access to pet food in pantries suggests further expansion of the pet food service into suburban and rural parts of Western Pennsylvania. Further research is needed to better understand the relationship between animal and human food insecurity as well as the wellbeing and mental and physical health benefits afforded by pet ownership for low-income owners.